Pemberian Diet Pasca Bedah Tinggi Energi Tinggi Protein, Rendah Serat pada Pasien Op. Laparatomy Appendectomy dengan Appendisitis Akut, Peritonitis Generalisata, Parotitis Epidemika - Nonda Rana Intanti (Syntax Idea)
Appendicitis is inflammation of the vermiform appendix which is a common cause of acute gastric pain and can develop into serious complications such as perforation and peritonitis. Proper nutritional food is very important for patients who are undergoing surgery and supports the healing process. This study aims to evaluate the standardized nutritional care process for pediatric patients diagnosed with post-operative acute appendicitis and generalized peritonitis. This research used an analytical observational design using a case study of a 6 year old boy who was treated at Lavalette Hospital, Malang City. Data collection was carried out using interviews, observations and anthropometric measurements. The patient's nutritional intake was analyzed using the 24-hour food recall method to evaluate nutritional needs that were met. The results showed that the energy and protein intake of post-surgery patients was still below the minimum recommended requirements. The diet provided was designed to be high in energy and protein and low in fiber to accelerate recovery. In addition, a decrease in leukocyte levels indicated post-surgery metabolic improvement, although there were indications of hypokalemia that required more attention. Standardized nutritional care is an important component in post-surgery patient care. Adequate nutrition will help restore nutritional status and increase endurance. Therefore, appropriate nutritional interventions must be implemented to support recovery and minimize the risk of complications in patients undergoing surgery for acute appendicitis and generalized peritonitis.